2011
DOI: 10.2334/josnusd.53.517
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sealing ability of mineral trioxide aggregate and Portland cement used as root-end filling materials

Abstract: Inadequate apical seal is the major cause of surgical endodontic failure. The root-end filling material used should prevent egress of potential contaminants into periapical tissue. The purpose of this study was to compare the sealing ability of four root-end filling materials: white mineral trioxide aggregate (MTA), gray MTA, white Portland cement (PC) and gray PC by dye leakage test. Ninety-six human single-rooted teeth were instrumented, and obturated with gutta-percha. After resecting the apex, an apical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 30 publications
2
35
0
1
Order By: Relevance
“…Comparison of MTA and Portland cement sealability using a bacterial leakage model [40] and fluid transport [37,41] exhibited similar results. This finding is in line with other results published on sealing ability of MTA and Portland cement [13,82].…”
Section: Mta and Portland Cementsupporting
confidence: 83%
“…Comparison of MTA and Portland cement sealability using a bacterial leakage model [40] and fluid transport [37,41] exhibited similar results. This finding is in line with other results published on sealing ability of MTA and Portland cement [13,82].…”
Section: Mta and Portland Cementsupporting
confidence: 83%
“…C. albicans has been found in the infected root canal and periapical pathologic tissues 18,19) . Both organisms may enter the pulp as contaminants from the oral microflora during rootcanal treatment and then enter the periapical region if an adequate root-end sealing is not provided 20) . Sen et al showed the penetration of cocci and yeasts into the dentinal tubules through their scanning electron microscopy-based study 6) .…”
Section: Discussionmentioning
confidence: 99%
“…Resin-containing composite materials release toxic monomers and shrink during polymerization (1). Since the introduction of mineral trioxide aggregate (MTA) (Dentsply Tulsa Dental Specialties, Tulsa, OK) into the field of root repair materials (2), calcium silicate-based materials have attracted considerable attention (3)(4)(5)(6)(7)(8) owing to their superior sealing ability, biocompatibility, regenerative capabilities, and antibacterial properties (4,6,(9)(10)(11)(12). Thus, they have been widely used both as endodontic repair materials and as dentin substitutes (13).…”
mentioning
confidence: 99%